The Adivasi question : issues of land, forest, and livelihood - Munshi, Indra; Tata Institute of Social Sciences (New Delhi : Orient BlackSwan, 2012)
With reference to India.
Series jointly executed by the Economic and political weekly and Tata Institute of Social Sciences
Includes bibliographical references.
Keywords: India; Indigenous peoples -- India -- Social conditions; Indigenous peoples -- India -- Economic conditions; Indigenous peoples -- Government policy -- India; Forestry law and legislation -- India